Identification Of AFLP Markers Associated With Round Heart Syndrome In Turkeys - Paxton, C.N.; Pierpont, M.E.; Kooyman, D.L. (International Journal of Poultry Science, 2005)
The Amplified Fragment Length Polymorphism (AFLP) method was used to identify 38 genetic markers that associate with either phenotypically normal or round heart turkeys, diagnosed by gross necropsy, from an inbred flock of Nicholas broad-breasted birds. Sixty-five polymorphisms were identified and analyzed by chi-square. A p-value of less than 0.05 determined markers that were kept and sequenced. Thirty-eight markers were identified, 19 that associated with the normal phenotype and 19 that associated with the round heart syndrome. The majority of the markers had a high A/T content, suggesting possible regulatory domains in which polymorphisms were occurring. Sequence Characterized Amplified Region (SCAR) primers were designed from marker sequences with the hopes of designing a simple Marker Assisted Selection (MAS) strategy. Work is ongoing to optimize these primers for SCAR analysis. With the development of a simple screening test, round heart may be greatly reduced or eliminated in commercial flocks.